Analysis of radiological features relative to histopathology in 42 skull-base chordomas and chondrosarcomas - (:unkn) unknown (ELSEVIER IRELAND LTD, 2006)
Chordomas and chondrosarcomas are malignant tumors that are reported to have similar clinical presentations and radiological features but different behaviors and outcomes. The aim of this retrospective study was to determine whether specific radiological features of skull-base chordomas or chondrosarcomas are correlated with histopathology, and thus allow preoperative diagnosis. The study involved 32 classic chordomas, 6 chondroid chordomas and 4 chondrosarcomas (42 tumors total). For each case, tumor size and extent, the detailed anatomy involved, and magnetic resonance imaging and computed tomography findings were analyzed. Tumor extent was assessed using a novel method that assessed presence/absence in 18 defined skull-base zones. The chondrosarcomas presented significantly earlier in life than the chordomas (means, 20.5 years versus 36 years, respectively). At time of diagnosis, the median tumor volume was 23 cm(3) (range, 1.2-78.8 cm(3)) and the mean tumor extent was 6.7 +/- 2.9 zones. There were no differences between chordomas and chondrosarcomas, or between the two chordoma subgroups, with respect to lesion volume or extent. Comparison of other imaging findings revealed no features that were diagnostic for either chordoma or chondrosarcoma. The data support previous claims that chondrosarcomas present earlier in life than chordomas, but this finding is not diagnostic. There is wide variation in the extent of skull-base chordomas and chondrosarcomas, and in the specific anatomical structures these tumors involve. None of the MRI or CT features of these tumors appear to be useful for differentiating chordomas from chondrosarcomas preoperatively. For surgical planning, specific, area-oriented definition of tumor extent might provide more useful information than tumor-type classification schemes. (c) 2006 Elsevier Ireland Ltd. All fights reserved.
Keywords: chordoma; chondrosarcoma; magnetic resonance imaging; computed tomography; MULTIDISCIPLINARY TEAM-APPROACH; FOLLOW-UP; CLIVAL; MANAGEMENT; MR; CT